8-oxoguanine DNA glycosylase 1 upregulation as a risk factor for obesity and colorectal cancer - Pilo, Jesús; García-Flores, Libia Alejandra; Clemente-Postigo, María Mercedes; Arranz-Salas, Isabel María; Alcaide, Julia; Ramos-Fernandez, Maria; Lozano-Castro, José; Boughanem Lakhal, Hatim; Kompella, Pallavi; Macías-González, Manuel (MDPI, 2023)
DNA damage has been extensively studied as a potentially helpful tool in assessing and preventing cancer, having been widely associated with the deregulation of DNA damage repair (DDR) genes and with an increased risk of cancer. Adipose tissue and tumoral cells engage in a reciprocal interaction to establish an inflammatory microenvironment that enhances cancer growth by modifying epigenetic and gene expression patterns. Here, we hypothesize that 8-oxoguanine DNA glycosylase 1 (OGG1)—a DNA repair enzyme—may represent an attractive target that connects colorectal cancer (CRC) and obesity. In order to understand the mechanisms underlying the development of CRC and obesity, the expression and methylation of DDR genes were analyzed in visceral adipose tissue from CRC and healthy participants. Gene expression analysis revealed an upregulation of OGG1 expression in CRC participants (p < 0.005) and a downregulation of OGG1 in normal-weight healthy patients (p < 0.05). Interestingly, the methylation analysis showed the hypermethylation of OGG1 in CRC patients (p < 0.05). Moreover, expression patterns of OGG1 were found to be regulated by vitamin D and inflammatory genes. In general, our results showed evidence that OGG1 can regulate CRC risk through obesity and may act as a biomarker for CRC.
Keywords: Genética; Cáncer colorrectal; ADN - Reparación; Cáncer - Aspectos genéticos; Colorectal cancer; CRC; Repair genes; OGG1; Methylation; Obesity; DNA repairs; Inflammation